2014
DOI: 10.1007/s40496-014-0036-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Prevalence, and Treatment of Halitosis

Abstract: Halitosis affects a large part of the population. Many of those that are affected suffer from this problem for a long time before they visit a professional halitosis clinic. Further, halitosis creates social and psychological disadvantages. Although halitosis has multifactorial origins, in nine out of ten cases the source can be found within the oral cavity. The most frequent intra-oral causes are tongue coating, gingivitis, and periodontitis, or a combination of these. A general dental practitioner is often f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 54 publications
0
26
0
11
Order By: Relevance
“…Los pacientes con halitosis psicosomática deben recibir atención por sicología (23,24). Prevalencia La prevalencia de la halitosis es incierta, principalmente por los diferentes métodos utilizados para evaluarla (25). Algunos estudios encuentran que más de la mitad de la población sufre de halitosis (26,27).…”
Section: Halitofobiaunclassified
See 1 more Smart Citation
“…Los pacientes con halitosis psicosomática deben recibir atención por sicología (23,24). Prevalencia La prevalencia de la halitosis es incierta, principalmente por los diferentes métodos utilizados para evaluarla (25). Algunos estudios encuentran que más de la mitad de la población sufre de halitosis (26,27).…”
Section: Halitofobiaunclassified
“…Se ha propuesto con poca evidencia el uso de metronidazol (12,49). También se ha sugerido el uso de saliva artificial para eliminar la resequedad y la remisión a otras especialidades (16,25).…”
Section: Tratamientounclassified
“…Halitosis has many causes, and aetiologies can be broadly divided into two categories: genuine halitosis; and pseudo-halitosis [2][3][4] . Genuine halitosis is detectable bad breath most commonly with an intra-oral cause, such as tongue coating, periodontitis and tooth decay; or less commonly with an extra-oral cause such as tonsillitis, gastrointestinal tract infections, diabetes, renal dysfunction and (in more sinister cases) cancers [1][2][3][4][5][6][7][8] . Pseudo-halitosis is rarer, has no detectable bad breath and is usually associated with a psychological origin 2,4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Bornstein et al . demonstrated that toothbrushing is an important factor in reducing the risk of severe halitosis; this might result from overlapping of the symptoms of genuine halitosis and pseudo‐halitosis with other ailments related exclusively to oral hygiene . Our findings emphasize the quality of oral hygiene procedures.…”
Section: Discussionmentioning
confidence: 56%
“…Genuine halitosis is a chronic and recurrent problem, affecting approximately 8–50% of people in the general population . It is estimated that up to 25% of adult patients experience persistent halitosis .…”
mentioning
confidence: 99%